2004
DOI: 10.1074/jbc.m404033200
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Respirasomes for the Assembly/Stability of Human Respiratory Chain Complex I

Abstract: We showed that the human respiratory chain is organized in supramolecular assemblies of respiratory chain complexes, the respirasomes. The mitochondrial complexes I (NADH dehydrogenase) and III (cytochrome c reductase) form a stable core respirasome to which complex IV (cytochrome c oxidase) can also bind. An analysis of the state of respirasomes in patients with an isolated deficiency of single complexes provided evidence that the formation of respirasomes is essential for the assembly/stability of complex I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
228
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 291 publications
(250 citation statements)
references
References 32 publications
17
228
3
2
Order By: Relevance
“…Our studies revealed that while complexes III and IV can assemble either as individual holoenzymes or by incorporation of free subunits into supercomplexes, the respirasomes constitute the structural units where complex I is assembled and activated, thus explaining the essentiality of the respirasomes for complex I function (Schagger et al, 2004). Importantly, this model aids explaining the structural interdependences among OXPHOS complexes, and why certain genetic defects affecting a single complex may lead to combined RC enzyme defects in patients.…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 75%
See 4 more Smart Citations
“…Our studies revealed that while complexes III and IV can assemble either as individual holoenzymes or by incorporation of free subunits into supercomplexes, the respirasomes constitute the structural units where complex I is assembled and activated, thus explaining the essentiality of the respirasomes for complex I function (Schagger et al, 2004). Importantly, this model aids explaining the structural interdependences among OXPHOS complexes, and why certain genetic defects affecting a single complex may lead to combined RC enzyme defects in patients.…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 75%
“…Such differences might be attributed to the nature of the mutation or the functional role of the OXPHOS mutated gene, and suggest that not all complexes III and IV structural genes are equally necessary to maintain complex I stability. The fact that complex III and complex IV can get assembled either as individual holoenzymes or by direct binding of free subunits to supercomplex assembly intermediates supports the existence of several independently-regulated assembly pathways for the biosynthesis of these two complexes, and explains why decreased complex I levels usually lead to isolated complex I deficiency in mammalian tissues (Acin-Perez et al, 2004;Schagger et al, 2004). However, once more exceptions have been reported (Budde et al, 2000;Ugalde et al, 2004;Saada et al, 2011), making necessary to gain more insight in the mechanisms that regulate the structural and functional interdependences between OXPHOS complexes.…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 97%
See 3 more Smart Citations